Versioning for the love of it : hip-hop culture in Aotearoa : a thesis presented in partial fulfilment of the requirements for the degree of Master of Arts in Social Anthropology at Massey University - Gibson, Lorena (Massey University, 2003)
This thesis seeks to explore the meaning of Hip-Hop for members of the Aotearoa Hip-Hop community. Based on participant-observation and interviews with members of the Hip-Hop community conducted during 2001-2003, this thesis provides an ethnographic study into what I have identified as the twelve key characteristics of Aotearoa Hip-Hop (authenticity, community, education, empowerment, history, knowledge, originality, representation, resistance, respect, skill and style). The thesis focuses on how these attributes are embodied in performance and in ongoing dialogues within the Hip-Hop community, as well as in the ways in which gender is negotiated in Aotearoa Hip-Hop, revealing the complex and sometimes contradictory nature of Hip-Hop culture in Aotearoa. It also considers the influence of the concept of whakapapa on Aotearoa Hip-Hop's distinctive historical trope, showing how ongoing dialogues within the Hip-Hop community occur at events and online, enacting Hip-Hop communities at these imagined and virtual sites.
Keywords: Hip-hop; Hip-hop culture, New Zealand